Pathogenetic mechanisms of postmenopausal osteoporosis formation and their relationship with cardiovascular pathology - G. V. Poryadin; A. N. Zakhvatov; D. V. Samarina (Бюллетень сибирской медицины, 2022)
Involutional hormonal processes characteristic of the postmenopause are accompanied by disorders that deteriorate the quality of life in the female population and lead to an increased risk of developing metabolic diseases of the bones and cardiovascular system. In modern medicine, it is extremely important to understand the pathogenesis of postmenopausal osteoporosis (PMO) in association with cardiovascular diseases, which are the main causes of mortality in the population.This review is devoted to determining the key aspects of the pathogenesis of PMO and identifying their relationships with cardiovascular pathology. Epidemiological data are assessed, the main mechanisms of PMO and vascular pathology development are considered, the fundamental role of hormone deficiency, immune dysregulation disorders, and disorders of macrophage polarization is described, and data on the association between the pathogenesis links of the studied pathological processes are analyzed.The obtained data will form a unified approach to reducing the growing prevalence of cardiovascular diseases and complications of PMO and contribute to the development of new research areas in disease prevention.